A New Class of Carbon Nanostructures for High‐Performance Electro‐Magnetic and ‐Chemical Barriers. Issue 22 (30th September 2021) - Park, Jae Hui; Oh, Yun Ji; Park, Dong Yoon; Lee, Joonsik; Park, Jae Seo; Park, Chong Rae; Kim, Jae Ho; Kim, Taehoon; Yang, Seung Jae
Abstract: It is of importance to explore a new carbon nanomaterial possessing vital functions to fulfill the high standards for practical achievement of the electromagnetic (EM) barrier for blocking EM waves and the electrochemical (EC) barrier as a functional separator for EC energy storage. Herein, facile synthesis of a new class of carbon nanostructures, which consist of interconnected N‐doped graphitic carbon nanocubes partially embedded by nickel nanoparticles, is described. The hollow interior of graphitic nanocube induces internal reflection of EM waves and confines active materials of EC energy storage. Nitrogen functionalities implanted in graphitic structure enhance electrical conductivity as well as improve chemical interaction with active materials. Furthermore, nickel nanoparticles in graphitic nanocube function as an EM wave‐absorbing material and an electrocatalyst for EC energy storage. Through comprehensive assessments, remarkable performances originating from distinctive nanostructures give new insights into structural design for the carbon nanostructure‐based high‐performance EM and EC barriers. Abstract : A novel carbon nanostructure is demonstrated as a promising key material for electromagnetic (EM) and electrochemical (EC) applications. Distinctive structural features originating from interconnected N‐doped graphitic nanocubes embedding nickel nanoparticles impart crucial functions desirable for the EM and EC barriers. Outstanding performances of the resulting carbon nanostructure are substantiated through comprehensive investigation and assessments for the EM and EC barriers.